High Performance Composite Polymer Electrolytes Doped With Spherical-Like and Honeycomb Structural Li0.1Ca0.9TiO3 Particles - Xiao, Wei; Wang, Zhiyan; Miao, Chang; Mei, Ping; Zhang, Yan; Yan, Xuemin; Tian, Minglei; Jiang, Yu; Liu, Jingjing (Frontiers in Chemistry, 2018)
The spherical-like and honeycomb structural Li0.1Ca0.9TiO3 particles are prepared by spray drying combined with following calcination confirmed by X-ray diffraction and scanning electron microscopy with energy dispersive X-ray spectrometer. The poly (vinylidene ﬂuoride-co-hexaﬂuoropropylene)-based composite polymer electrolytes doped with the particles are fabricated by phase inversion and activation processes. The characterization results show that the as-prepared composite polymer electrolyte membranes possess the smoothest surface and richest micropores with the lowest crystallinity with adding the particles into the polymer matrix, in which the ionic conductivity and lithium ion transference number at room temperature can reach up to 3.947 mS cm-1 and 0.4962, respectively. The interfacial resistance can be quickly stabilized at 508 Ω after 5 days storage and the electrochemical working window is up to 5.2 V. Moreover, the mechanical strength of the membranes gains much improvement without lowering the ionic conductivity. Furthermore, the assembled coin cell can also deliver high discharge specific capacity and steady cycle performance at different current densities. Those excellent properties can be attributed to the unique structure of the as-synthesized spherical-like and honeycomb structural Li0.1Ca0.9TiO3 particles, which can ensure it as a promising polymer electrolyte for the lithium ion battery.